Swedish primary healthcare practitioners' perspectives on the impact of arts on prescription for patients and the wider society: a qualitative interview study - Anita Jensen; Hilary Bungay (BMC, 2021)
Abstract Background There is growing evidence that participating in arts activities are beneficial for mental health and wellbeing. Many patients attending primary care services have mental ill-health or social issues that healthcare practitioners currently do not have adequate ways of supporting. This study set out to explore the perspectives of primary healthcare practitioners on Arts on Prescription (AoP) as an additional referral pathway. Methods A qualitative exploratory descriptive approach within an interpretive framework using semi-structured interviews was used to explore healthcare practitioners' perspectives and experiences of AoP programmes in Sweden. Ten interviews were conducted with healthcare practitioners in primary care. Data were analysed using an inductive thematic approach. Results The healthcare practitioners interviewed, recognised the need for more holistic approaches to care for those with mental health issues. They perceived that AoP is beneficial for patients in terms of motivation, creating routines, providing social interactions, and increasing self-esteem. In addition, AoP was felt to have the potential to impact upon current service provision and wider society. However, whilst the opportunity to refer patients to AoP in conjunction with conventional treatments was valued, participants reported that time pressures on practitioners and the continuing dominance of the medical model of care were barriers to wider acceptance amongst practitioners at the present time. Conclusions AoP enabled primary healthcare practitioners to offer an additional pathway for patients that is an adjunct to the traditional care pathway. However, the programmes tend to be project-based and often time limited. For programmes to be sustainable and be included as part of a wider range of interventions available to healthcare practitioners' suitable levels of funding would be required.